Evaluating the Mystery of ‘Brushy Bill’ Roberts (aka., Billy the Kid) as a Case of Extreme Celebrity Worship - Houran, James; Sheridan, Lorraine; Dagnall, Neil (Journal of Scientific Exploration, 2023)
‘Brushy Bill’ Roberts gained notoriety in 1950 for identifying himself as the presumably deceased outlaw ‘Billy the Kid.’ We hypothesized that his case reflected extreme celebrity worship, which involves psychological absorption with a target celebrity and potential fantasy-reality breakdowns. A blinded expert panel mapped Roberts’ claims, activities, and circumstances against the three phases of celebrity worship and their known correlates. Outcomes from this exercise suggested that: (a) his reported attitudes and behaviors equated to an above-average score on the Celebrity Worship Scale (McCutcheon, Lange, & Houran, 2002), (b) his identity as the Kid unfolded somewhat similarly to the behavioral progression of celebrity worship, and (c) he ostensibly had the most psychosocial risk factors for the ‘Entertainment-Social’ level of celebrity worship, though many were also noted for the more extreme ‘Intense-Personal’ and ‘Borderline Pathological’ phases. These results imply that Roberts might have consciously adopted Billy the Kid as an alter ego primarily for leisure and escapism, although this construction perhaps evolved to include more compulsory or addictive aspects.